Penerapan dan Evaluasi Program Green Campus dalam Meningkatkan Pelayanan Akademik di Fakultas Ekonomi dan Bisnis Universitas Andalas - Hidayani, Sari Dewi; Chandra, Dedy; Lita, Ratni Prima (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2024)
Higher education institutions bear a moral responsibility to foster an environmentally conscious culture through sustainable campus management. This study aims to evaluate the implementation of the Green Campus Program at the Faculty of Economics and Business, Universitas Andalas (FEB UNAND), to enhance the quality of sustainable academic services. The research employs a quantitative approach using purposive sampling, involving 75 respondents from various campus elements, including lecturers, administrative staff, and students. Data were collected through surveys and questionnaires addressing awareness, participation, and program challenges.The findings reveal that while the majority of respondents recognize the benefits of the Green Campus initiative, its implementation remains limited to tree-planting competitions. Approximately 96% of respondents agree that the program's scope should be expanded to include reducing plastic waste, enhancing energy efficiency, and waste management. Key challenges include insufficient supporting facilities, resistance to change, and suboptimal socialization.The study recommends a holistic strategy encompassing education, provision of eco-friendly facilities, institutional policy strengthening, and integration of social norms to ensure program sustainability. These findings are expected to serve as a reference for other institutions in implementing Green Campus practices to support environmental sustainability and improve academic service quality. Abstrak Perguruan tinggi memiliki tanggung jawab moral dalam membentuk budaya berwawasan lingkungan melalui pengelolaan kampus yang ramah lingkungan. Penelitian ini bertujuan mengevaluasi penerapan Program Green Campus di Fakultas Ekonomi dan Bisnis Universitas Andalas (FEB UNAND) untuk meningkatkan kualitas pelayanan akademik yang berkelanjutan. Metodologi penelitian menggunakan pendekatan kuantitatif dengan purposive sampling, melibatkan 75 responden dari berbagai elemen kampus, seperti dosen, tenaga kependidikan, dan mahasiswa. Data dikumpulkan melalui survei dan kuesioner terkait kesadaran, partisipasi, dan hambatan program.Hasil penelitian menunjukkan bahwa mayoritas responden menyadari manfaat Green Campus, tetapi implementasinya terbatas pada lomba penghijauan. Sebanyak 96% responden setuju bahwa fokus program perlu diperluas, mencakup pengurangan limbah plastik, efisiensi energi, dan pengelolaan limbah. Hambatan utama adalah kurangnya fasilitas pendukung, resistensi terhadap perubahan, dan sosialisasi yang belum optimal.Penelitian ini merekomendasikan strategi holistik, termasuk edukasi, penyediaan fasilitas ramah lingkungan, penguatan kebijakan institusi, dan integrasi norma sosial untuk keberlanjutan program. Hasil ini diharapkan dapat menjadi panduan bagi institusi lain dalam mengimplementasikan praktik Green Campus untuk mendukung keberlanjutan lingkungan dan peningkatan mutu layanan akademik.